2021
DOI: 10.1016/j.curtheres.2021.100633
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Prevention Practices Toward Coronavirus Disease 2019 in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Background Coronavirus disease is a major global public health problem. The contagious disease caused by a newly discovered coronavirus, coronavirus disease 2019 (COVID-19), was declared a pandemic following the outbreak of cases of respiratory illness in 2019. While studies assessed COVID-19 knowledge, attitude, and practice in Ethiopia the findings were highly variable and inconsistent. 1 , 2 , 3 , 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
5
5
1
1
Order By: Relevance
“…In the current study, the overall pooled level of poor COVID-19 preventive practice in Ethiopia was 51.60% (95% CI: 40.30–62.90). This finding was consistent with previous systematic reviews and meta-analyses in Ethiopia that found the pooled prevalence of poor COVID-19 prevention practice to be 58.3% [ 40 ], 40% [ 41 ] and 47% [ 42 ]. However, when compared with global systematic reviews and meta-analyses, the pooled proportion of poor COVID-19 preventive practice in Ethiopia is higher, with less than a 30% pooled level of poor COVID-19 prevention practice globally [ [43] , [44] , [45] , [46] ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, the overall pooled level of poor COVID-19 preventive practice in Ethiopia was 51.60% (95% CI: 40.30–62.90). This finding was consistent with previous systematic reviews and meta-analyses in Ethiopia that found the pooled prevalence of poor COVID-19 prevention practice to be 58.3% [ 40 ], 40% [ 41 ] and 47% [ 42 ]. However, when compared with global systematic reviews and meta-analyses, the pooled proportion of poor COVID-19 preventive practice in Ethiopia is higher, with less than a 30% pooled level of poor COVID-19 prevention practice globally [ [43] , [44] , [45] , [46] ].…”
Section: Discussionsupporting
confidence: 92%
“…Poor COVID-19 preventive practice has been found to be more prevalent in community-based studies than in studies of patients with chronic disease patients and visitors to health services. This may be due to good institutional preventative procedures compared with practices in communities; this finding is similar to the results of Azene et al [ 40 ]. However, a subgroup analysis revealed that 61.65% of health professionals had a significant degree of inadequate preventive practice.…”
Section: Discussionsupporting
confidence: 90%
“…A study by El-Elimat et al (2021) examined the Jordanian population's acceptance of COVID-19 vaccines, stating that younger individuals were more likely to accept COVID-19 vaccinations. In addition to this, Azene et al (2021) found that in Ethiopia, there have been insufficient preventive measures on COVID-19. In another study by Acharya et al (2021) on the attitude of immigrants toward COVID-19 vaccine acceptance in South Korea, more than half of the research respondents (55.3%) were willing to get COVID-19 vaccinations, with their main concern being vaccine safety.…”
Section: Introductionmentioning
confidence: 95%
“…Given the nature of the COVID-19 pandemic, regular update of scientific literature is essential for initiating empirical evidence on interventions and strategies to tackle the COVID-19 pandemic more conveniently. For this purpose, a comprehensive and timely updated systematic evaluation of existing evidence is highly needed, whereas a few systematic review and meta-analysis has been published on the KAP of COVID-19 ( 15 , 17 19 ). Notwithstanding, region- or country-based systematic reviews lack; for instance, Ethiopia ( 17 , 20 ) and the United States ( 20 ) have reported publishing country-based systematic reviews on the KAP of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, a comprehensive and timely updated systematic evaluation of existing evidence is highly needed, whereas a few systematic review and meta-analysis has been published on the KAP of COVID-19 ( 15 , 17 19 ). Notwithstanding, region- or country-based systematic reviews lack; for instance, Ethiopia ( 17 , 20 ) and the United States ( 20 ) have reported publishing country-based systematic reviews on the KAP of COVID-19. Furthermore, knowledge and public perception being culture-based, interventions should focus on the data from the respective culture.…”
Section: Introductionmentioning
confidence: 99%